Supply chain risk management in Brazil: analysis of the recycling sector - Barbuio, Claudia Alessandra (2018)
The research objective of this dissertation is to identify the main risks and challenges that affect the recycling industry in Brazil and the practices adopted by this industry’s players to face them. The recycling industry is an expanding sector that still presents many obstacles. an exploratory research based on one case study, is developed with the aim of identifying the risks specifically related to recycling in Brazil and the strategies that have been implemented by recycling players in Brazil. The case selected for this study is TriCiclos, a company based in Brazil that is inserted in the recycling supply chain of the city of São Paulo. The data collected on this company through interviews and observations are analyzed in the light of the literature review on the topic to obtain results in terms of strategy definition for facing risks. The contribution of this work to management and organizations will be a thorough review and presentation of possible improvements, based on interviews results, of those strategies used to stem risks away and build an effective recycling supply chain considering the barriers peculiar to the recycling industry. The final purpose is to create a basis for a future discussion on the best strategy for realizing an efficient integration of the different players in the recycling supply chain.